QT Prolongation in Cancer Patients - Kim, Peter; Masha, Luke; Olson, Amanda; Iliescu, Cezar; Karimzad, Kaveh; Hassan, Saamir; Palaskas, Nicolas; Durand, Jean-Bernard; Leung, Cheuk Hong; Lopez-Mattei, Juan (Frontiers in Cardiovascular Medicine, 2021)
Background QT prolongation and torsades de pointes pose a major concern for cardiologists and oncologists. Although cancer patients are suspected to have prolonged QT intervals, this has not been investigated in a large population. This purpose of this study was to analyze the QT interval distribution in a cancer population and compare it to a non-cancer population in the same institution. Methods The study was a retrospective review of 221,332 ECGs performed in 82,410 patients (51.8% women and 48.2% men) from January 2009 to December 2013 at the University of Texas MD Anderson Cancer Center. Pharmacy prescription data was also collected and analyzed during the same time period. The first reported ECGs were collected from all cancer patients and non-cancer, stem cell donors from January 2009 to December 2013. Results After QT correction for heart rate by the Fridercia formula (QTcF), the mean and 99% percentile QTc for cancer patients were 416 ms and 483 ms, respectively. These were significantly longer than the normal stem cell donors, 407 ms and 458 ms, p < 0.001, respectively. Among the cancer patients, the QTc was longer in the inpatient setting when compared to both outpatient and emergency center areas. The most commonly prescribed QT prolonging medications identified were ondansetron and methadone. Conclusion Our study demonstrates the significantly longer QTc in cancer patients, especially in the inpatient setting. Frequently prescribed QT prolonging medications such as antiemetics and analgesics may have a causative role in QT prolongation seen in our cancer hospital.